Post a New Question


posted by on .

Composition of Functions

f o g(x)=f(g(x)) --> I know that this is eqivalent to f(g(x))

Given f(x) = 2x+1, and g(X) = 3x+1 find:f o g(x)=f(g(x))

This is what I did, but I don't think Ive solved it correctly

f(g(x)) = f(x-3)
f(x-3) = 1(x-3)-3x+2
f(g(x)) = -2x-1

The perimeter P of a square and the area A of a square r functions of its side length S. write area as function of Perimeter. ?

Also write out the square's area as function of length of its diagonal.

  • Pre-Calculus - ,

    f(g) = 2g+1 = 2(3x+1)+1 = 6x+3
    dunno where you got x-3

    P = 4s
    A = s^2 = (P/4)^2 = P^2/16

    d = s√2
    A = s^2 = (d/√2)^2 = d^2/2

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question